(3GdcTa Yf eLGhRg gPg GdCeI GdCda hLhGH GdEeGe GdSjhWi Ydi SDGd aj GdegOis - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg hcai hSdGe Ydi YHGOg GdPjf GUWai hHYO abO cKQ GdSDGd Yf GdMOjK GdeTghQ Ydi CdSfg GdfGS Cf GdfHi dG jecK ai bHQg Cda SfI hCfG CLjH Cfg HGWd dG CUd dg s
(3BNQgG (B:s
(3heef GSJKfi Gddg eaYhdg Edi ef TGA Gddg hCeG GdedGFcI ajehJhf HGdfU hGdELeGY s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B17s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Hg fbhd Ydi ghGeTg MOjKs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdeLGejYs